Situated learning in community environments (SLICE): Systems design of an immersive and integrated curriculum for community-based learning. (2nd January 2023) - Taoube, Linda; Khanna, Priya; Schneider, Carl; Burgess, Annette; Bleasel, Jane; Haq, Inam; Roberts, Chris
Abstract: Purpose: We sought to design a micro-curriculum to structure supervised clinical placements for junior medical students within a variety of community-based settings of differing clinical disciplines. Given the gaps in the literature, this paper reflects on the opportunities and challenges of our design, implementation, and evaluation strategies in constructing an integrated task-based micro-curriculum for interprofessional community-based learning in year 2 of a four-year graduate entry program. Methods: The design was informed by a systems thinking framework and guided by contemporary curricular theories on self-directed and interprofessional learning. Extensive consultations with stakeholders were undertaken. Alignment with relevant national level documents and curricular frameworks was ensured. Results: The systems thinking approach provided first, an experience of applying thinking tools for a deeper understanding of how various parts of this micro-curriculum and subsystems should be integrated. Second, applying the toolkit uncovered tension points on which leverage could optimise future enhancements. Eighteen types of health professions were recruited including 105 general practitioners and 253 healthcare practitioners from a range of disciplines. Conclusion: Systems thinking allows for the identification of various interacting elements within the curriculum to be considered as part of an integrated whole. Insights from this model could inform the design of similar innovative curricula.